2012
DOI: 10.1111/j.1746-1561.2012.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Academic Performance in Hong Kong Adolescents

Abstract: Poorer academic performance was associated with sleep debt, and symptoms of insomnia and OSA. Sleep compensation but not naps may be a protective factor of poor academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 41 publications
5
48
2
1
Order By: Relevance
“…Because sleep factors had different influence on academic achievement (showing sleepiness the strongest relation, followed by sleep quality and sleep duration) (Dewald et al, 2010), this could explain the weak relationship between time in bed on weekdays and GPA (r = 0.13). Also, probably, in samples of adolescents with dramatic lack of night sleep duration the relation between time in bed and GPA would be large (Mak et al, 2012; Similar to results that were meta-analyzed by Astill et al (2012), intelligence test scores appeared to be a consistent trait that was unaffected by variations in sleep duration. The lack of relationship between time in bed and primary mental abilities could be explained by the fact that adolescents have a more elaborate arsenal of brain mechanisms to support synaptic downscaling during sleep period than do adults, whose mechanisms may have become much more dependent on sleep (Astill et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Because sleep factors had different influence on academic achievement (showing sleepiness the strongest relation, followed by sleep quality and sleep duration) (Dewald et al, 2010), this could explain the weak relationship between time in bed on weekdays and GPA (r = 0.13). Also, probably, in samples of adolescents with dramatic lack of night sleep duration the relation between time in bed and GPA would be large (Mak et al, 2012; Similar to results that were meta-analyzed by Astill et al (2012), intelligence test scores appeared to be a consistent trait that was unaffected by variations in sleep duration. The lack of relationship between time in bed and primary mental abilities could be explained by the fact that adolescents have a more elaborate arsenal of brain mechanisms to support synaptic downscaling during sleep period than do adults, whose mechanisms may have become much more dependent on sleep (Astill et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
“…This situation is dramatic among Chinese, Korean, Japanese and Asian adolescents, who generally have later bedtimes than those from Europe and North America (Mak et al, 2012;Rhie & Chae, 2011). Adolescent's sleep delay is relatively long compared to children's and adults', leading to shorter time in bed during the week due to the early start time of school.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in accordance with a previous report associating weekend oversleep with academic performance, although 76% of the participants in that study reported sleeping more than 7 hours per night. 24 On the contrary, sleep duration and subjective sleepiness did not correlate with academic performance. Several studies have associated academic performance and short sleep duration 25 or subjective sleepiness 26 in adolescents, whereas other studies failed to detect these relationships.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported high levels of stress and mental health problems such as insomnia and self-injury among students in Hong Kong [71][72][73] . Risk factors of such problems included…”
Section: Discussionmentioning
confidence: 98%